2012
DOI: 10.3390/molecules17033484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary Investigations of the siRNA Delivery Potential of Novel, Single-Chain Rigid Cationic Carotenoid Lipids

Abstract: Abstract:The success of nucleic acid delivery requires the development of safe and efficient delivery vectors that overcome cellular barriers for effective transport. Herein we describe the synthesis of a series of novel, single-chain rigid cationic carotenoid lipids and a study of their preliminary in vitro siRNA delivery effectiveness and cellular toxicity. The efficiency of siRNA delivery by the single-chain lipid series was compared with that of known cationic lipid vectors, 3β-[N-(N',N'-dimethylaminoethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…375 In 2012, Pungente et al developed five carotenoids-derived single-tailed rigid cationic lipids, which were expected to be capable of selfassembling and delivering siRNA efficiently. 376 As shown in Then, these lipids were obtained via esterification followed by amination or quaternization. Results indicated that these singletailed rigid cationic lipids were able to deliver siRNA to eukaryotic cells in vitro.…”
Section: Cationic Lipidsmentioning
confidence: 99%
“…375 In 2012, Pungente et al developed five carotenoids-derived single-tailed rigid cationic lipids, which were expected to be capable of selfassembling and delivering siRNA efficiently. 376 As shown in Then, these lipids were obtained via esterification followed by amination or quaternization. Results indicated that these singletailed rigid cationic lipids were able to deliver siRNA to eukaryotic cells in vitro.…”
Section: Cationic Lipidsmentioning
confidence: 99%
“…Very recently Sliwka et al . synthetized some new cationic carotenoid lipids, where a quaternary ammonium moiety is responsible for the amphipatic character of the molecules [12,13].…”
Section: Hydrophilic Salts Of Carotenoid Estersmentioning
confidence: 99%
“…The cholesterol-based cationic lipid has been used as the major hydrophobic domain of liposomes for gene delivery due to being less toxic than other cationic lipids [ 16 ]. Many cholesterol-based cationic lipids have been synthesized, among which 3β-[ N -( N ', N '-dimethylaminoethyl)-carbamoyl] cholesterol (DC-Chol, Figure 1 ) showed efficient transfection in gene delivery and was used as the commercially available liposome reagent [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%